Profile of children with cerebral palsy at a tertiary hospital in eastern Nepal - Shipra Chaudhary; Nisha Keshary Bhatta; Prakash Poudel; Jyoti Agrawal; Rosan Prasad Shah Kalawar; Jitendra Prasad Jayswal (BMC, 2022)
Abstract Background The clinical spectrum of Cerebral palsy (CP) can differ in various places depending upon knowledge of the people and resources for prevention, diagnosis and management. Although studied extensively in high-resource countries, adequate data related to CP from resource-constraint settings are lacking. This study aims to describe the profile of children with CP at a tertiary care center in eastern Nepal. Methods This was a hospital-based cross-sectional descriptive study done from 2017 to 2018. Children 6 months to 15 years who presented with CP were enrolled and their clinical details recorded and described. Results Amongst 110 children with CP, 74.54% were male. Majority (76.36%) were 5 years or below with the median age being 3(2.00-4.75) years. Children with spastic quadriplegia (44.44%) and Gross Motor Function Classification System level III (41.81%) were most common. Etiologically, perinatal factors (64.54%) like perinatal asphyxia (35.45%) and prematurity (20.90%) and postnatal infections (25.45%) were common. The common comorbidities were intellectual disability (71.81%) and epilepsy (66.36%). The main treatment modalities were: antiepileptics (59.09%) and centre-based physiotherapy sessions (35.45%). School education was provided in 23.07% with special education in 11.53%. Conclusions This study describes the profile of CP at our centre in eastern Nepal. Predominance of perinatal complications and postnatal infections points towards the urgent need to further improve the perinatal and neonatal health care delivery system and practices.